SISTEM IRIGASI PERTANIAN BERBASIS MIKROKONTROLER ARDUINO UNO DI DESA WANAJAYA CIKARANG KABUPATEN BEKASI: SISTEM IRIGASI PERTANIAN BERBASIS MIKROKONTROLER ARDUINO UNO DI DESA WANAJAYA CIKARANG KABUPATEN BEKASI - Asep Sumantri (Jurnal Ilmu Komputer, 2022)
Irrigation is an important thing in the agricultural process. The need for adequate water greatly affects plant growth. Provision of water with a certain irrigation system is identical to the type and requirement of water for each plant. The limited availability of water in the irrigation process, especially during the dry season, makes farmers have to do various ways so that plants can still get water according to their needs. The agricultural irrigation system based on the Arduino Uno microcontroller is one way of dealing with this problem. Where by utilizing IoT (Internet of Things) technology the system will run automatically based on sensors. Keywords— Irigasi Pertanian, Arduino UNO, Soil Moisture Sensor, NodeMCU, Thinger.io, Evolutionary Prototype.